MOFs-loaded zeolite molecular sieve composite material and preparation method and application thereof
By loading silver ions on the zeolite molecular sieve and growing Ag-MOFs in situ, zeolite molecular sieve composites with high specific surface area and high efficiency radon adsorption capacity were prepared, which solved the problem of low efficiency of existing radon adsorption materials.
Patent Information
- Application Number
- CN202410390355.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-02
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-04-02
AI Technical Summary
The existing radon adsorption materials have a small specific surface area, and the radon adsorption effect is poor and the efficiency is low.
By immersing the modified silver ions with silver nitrate solution, Ag-MOF is then grown in situ, and the pore size advantages of zeolite molecular sieve and MOFs are coordinated to prepare MOFs-loaded zeolite molecular sieve composites.
The adsorption capacity of radon gas is significantly improved. The specific surface area of the composite material is as high as 1298-1425m2/g, the absorption efficiency of radon gas reaches 81.4-93.5%, and the semi-penetration time is 55-83min.
Smart Images

Figure CN118356913B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas adsorption materials, and in particular to a zeolite molecular sieve composite material loaded with MOFs, and a preparation method and application thereof. Background Art
[0002] Radon gas ( 222 Rn, T 1 / 2 = 3.8235 days) is a radioactive noble gas that is ubiquitous in the environment. 238 U / 226 As part of the Ra decay chain, it has been found to contribute significantly to the radiation dose to the public. Although the concentration of Rn in the air is extremely low, Rn can enter the human body through inhalation of the respiratory tract and diet. The alpha particles produced by its decay produce a radioactive stochastic effect on the human respiratory system, which can induce lung cancer, making Rn one of the main causes of lung cancer. Rn and its decay progeny were identified as human carcinogens (Group I) by the International Agency for Research on Cancer in 2012. The World Health Organization International Radon Project recommends a reference level of radon concentration of 100 Bq / m 3 , to minimize the health risks of indoor radon exposure.
[0003] Using porous materials to adsorb radon is one of the methods to remove radon. The effect of porous materials on gas adsorption is mainly reflected in two aspects: first, the pore size of porous materials will have a direct impact on gas adsorption and separation. When the gas molecule size is larger than the adsorbent pore size, it cannot be adsorbed. When the gas molecule size is much smaller than the adsorbent pore size, it is easy to escape from the pore. Only when the gas molecule size is equal to or slightly smaller than the adsorbent pore size can a strong adsorption effect be produced. Existing simulation calculations and experimental studies have shown that the pore size is The uniform porous material has good Rn adsorption selectivity; secondly, the functional groups and special sites on the porous material will affect the material adsorption performance. Studies have shown that Ag + , graphite surface electric field, etc. will produce polarization effect on Rn, thereby enhancing the interaction with Rn and improving its adsorption capacity. However, existing radon gas adsorption materials often have the problems of small specific surface area, poor radon gas adsorption effect and low efficiency. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a zeolite molecular sieve composite material loaded with MOFs and a preparation method and application thereof, so as to at least solve the problems of small specific surface area, poor radon gas adsorption effect and low efficiency of existing radon gas adsorption materials.
[0005] The present invention solves the above technical problems by the following technical means:
[0006] In the first aspect, the present invention provides a zeolite molecular sieve composite material loaded with MOFs, comprising the following raw materials: solid AgNO3, 2-aminoterephthalic acid, N,N-dimethylformamide, and Ag-zeolite molecular sieve, wherein the dosage ratio of the solid AgNO3, 2-aminoterephthalic acid, N,N-dimethylformamide, and Ag-zeolite molecular sieve is (0.012-0.037) mol: (0.009-0.026) mol: (50-300) ml: (20-75) g.
[0007] In combination with the first aspect, in some embodiments, the Ag-zeolite molecular sieve is prepared by soaking the zeolite molecular sieve in a 5-20 wt % silver nitrate solution.
[0008] In a second aspect, the present invention provides a method for preparing a zeolite molecular sieve composite material loaded with MOFs, comprising the following steps:
[0009] The zeolite molecular sieve is added into the silver nitrate solution and soaked for 3 to 5 hours, and filtered to obtain the Ag-zeolite molecular sieve;
[0010] Solid AgNO3 and 2-aminoterephthalic acid were dissolved in N,N-dimethylformamide, and Ag-zeolite molecular sieve was added. The mixture was shaken and stirred evenly. The obtained mixture was transferred to a stainless steel high-pressure reactor and heated at 110-130°C for 12-24 hours. After the reaction, the product was cooled and centrifuged to collect the powder. The powder was then immersed in methanol solution for washing and vacuum dried at 80-120°C for 6-10 hours to obtain a zeolite molecular sieve composite material loaded with MOFs.
[0011] In combination with the second aspect, in some embodiments, the concentration of silver nitrate in the silver nitrate solution is 5-20 wt %.
[0012] In combination with the second aspect, in some embodiments, the usage ratio of the solid AgNO3, 2-aminoterephthalic acid and N,N-dimethylformamide is (1.2-3.7) mol: (0.9-2.6) mol: (50-300) ml.
[0013] In combination with the second aspect, in some embodiments, the usage ratio of the solid AgNO3, 2-aminoterephthalic acid, N,N-dimethylformamide, and Ag-zeolite molecular sieve is (1.2-3.7) mol: (0.9-2.6) mol: (50-300) ml: (20-75) g.
[0014] In combination with the second aspect, in some embodiments, the preparation method further includes placing the obtained MOFs-loaded zeolite molecular sieve composite material in a muffle furnace, using nitrogen as a protective gas, and calcining and activating it at 160 to 200° C. for 4 to 8 hours.
[0015] In a third aspect, the present invention further provides the use of the MOFs-loaded zeolite molecular sieve composite material described in the first aspect or the MOFs-loaded zeolite molecular sieve composite material prepared by the preparation method described in the second aspect in radon gas adsorption materials.
[0016] The present invention uses zeolite molecular sieve as a base material, impregnates and modifies the zeolite molecular sieve with a silver nitrate solution to load a certain amount of silver ions, and then grows the material MOFs in situ, synergizing the pore size advantages of the zeolite molecular sieve and MOFs to prepare a composite material that is beneficial to the radon gas adsorption effect. According to the test, the zeolite molecular sieve composite material loaded with MOFs of the present invention has a large specific surface area of up to 1298-1425m 2 / g.
[0017] The present invention adopts a method of pre-impregnating the zeolite molecular sieve, whereby Ag can easily enter the molecular sieve through ion exchange, so that Ag is distributed on the surface of the zeolite molecular sieve and inside and outside the pores. + , the in-situ grown Ag-MOF can be more evenly dispersed on the zeolite material, and the structure is stable and not easy to peel off, which ultimately makes the adsorption effect of the composite material more stable and effective. According to the test, the absorption efficiency of the invented MOFs-loaded zeolite molecular sieve composite material for radon gas can reach 81.4-93.5%, with a high adsorption efficiency and a half-penetration time of 55-83 minutes, reflecting its high adsorption and binding capacity for radon gas.
[0018] The present invention selects Ag-MOF and utilizes the polarization effect of Ag on Rn, thereby enhancing the adsorption effect of the composite material prepared by the present invention on radon gas. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is the isothermal adsorption curve diagram of the materials prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The raw materials, equipment or instruments used, if no manufacturer is specified, are all conventional products that can be purchased on the market.
[0022] Zeolite molecular sieves are tetrahedral units formed by connecting the primary structural unit -TO4 (T is usually Si, Al, P, B, etc.) with the help of oxygen bridges in a shared vertex manner. Natural zeolite was first discovered by Swedish mineralogist Cronstedt in the 1750s and 1760s. Its main component is aluminosilicate; but due to the limited number of natural zeolites and the limitations of their morphology and pore structure, they cannot meet the large-scale needs of industry, so artificial zeolites are needed in industrial production. Zeolite molecular sieves have the advantages of high packing density, narrow pore size distribution range, and strong selective adsorption, and are a potential Rn adsorbent.
[0023] The present invention uses zeolite molecular sieve as a base material and selects titanosilicate with more cation exchange sites. According to the Rn adsorption principle and the research reports on molecular sieves for Rn adsorption and separation at home and abroad, SSZ-13, ZSM-5 and ETS-10 are typical molecular sieves with different pore sizes and strong ion exchange capacity. The zeolite molecular sieve is impregnated and modified with a silver nitrate solution so as to load a certain amount of silver ions. Then, Ag-MOF is in situ grown on the Ag-zeolite molecular sieve to finally obtain a zeolite molecular sieve composite material loaded with MOFs.
[0024] The MOFs-loaded zeolite molecular sieve composite material of the present invention comprises the following raw materials: solid AgNO3, 2-aminoterephthalic acid, N,N-dimethylformamide, Ag-zeolite molecular sieve, wherein the usage ratio of solid AgNO3, 2-aminoterephthalic acid, N,N-dimethylformamide, Ag-zeolite molecular sieve is (0.012-0.037) mol: (0.009-0.026) mol: (50-300) ml: (20-75) g. The Ag-zeolite molecular sieve is prepared by immersing the zeolite molecular sieve in a 5-20wt% silver nitrate solution.
[0025] The method for preparing the MOFs-loaded zeolite molecular sieve composite material of the present invention comprises the following steps:
[0026] The zeolite molecular sieve is added into the silver nitrate solution and soaked for 3 to 5 hours, and filtered to obtain the Ag-zeolite molecular sieve;
[0027] Solid AgNO3 and 2-aminoterephthalic acid were dissolved in N,N-dimethylformamide, and Ag-zeolite molecular sieve was added. The mixture was shaken and stirred evenly. The obtained mixture was transferred to a stainless steel high-pressure reactor and heated at 110-130°C for 12-24 hours. After the reaction, the product was cooled and centrifuged to collect the powder. The powder was then immersed in methanol solution for washing and vacuum dried at 80-120°C for 6-10 hours to obtain a zeolite molecular sieve composite material loaded with MOFs.
[0028] The following is a detailed description of the MOFs-loaded zeolite molecular sieve composite material and its preparation method by using Examples 1-5:
[0029] Example 1
[0030] The preparation method of the MOFs-loaded zeolite molecular sieve composite material of this embodiment is as follows:
[0031] Use 10wt% silver nitrate solution to impregnate an appropriate amount of zeolite molecular sieve. Simply immerse the zeolite molecular sieve completely in the silver nitrate solution for 3 hours to obtain Ag-zeolite modified material; dissolve 3.79g AgNO3 and 2.93g 2-aminoterephthalic acid in 100ml N,N-dimethylformamide; then add 30g of Ag-zeolite molecular sieve, shake and stir evenly, transfer the resulting mixture to a stainless steel autoclave, heat at 110℃ for 12h, cool the product after the reaction, centrifuge, collect the powder, and then immerse the powder in methanol solution for several times, and finally vacuum dry at 80℃ for 6h to obtain the final product, MOFs-loaded zeolite molecular sieve composite material. The final product is placed in a muffle furnace, calcined and activated at 160℃ for 4h under nitrogen as protective gas for testing.
[0032] Comparative Example 1
[0033] 3.79g AgNO3 and 2.93g 2-aminoterephthalic acid were dissolved in 100ml N,N-dimethylformamide, and the resulting mixture was transferred to a stainless steel autoclave, heated at 110°C for 12h, and the product was cooled and centrifuged after the reaction, and the powder was collected, and then immersed in methanol solution for washing several times, and finally vacuum dried at 80°C for 6h to obtain the final product, Ag-MOF composite material. The final product was placed in a muffle furnace, calcined and activated at 160°C for 4h under nitrogen as protective gas for testing.
[0034] The materials prepared in Example 1 and Comparative Example 1 were characterized by using a BET specific surface area analyzer. The N2 adsorption curves are shown in FIG. Figure 1 As shown, the adsorption results are shown in Table 1. The test results prove that the Ag-MOF@zeolite molecular sieve composite material has a relatively larger specific surface area.
[0035] Example 2
[0036] The preparation method of the MOFs-loaded zeolite molecular sieve composite material of this embodiment is as follows:
[0037] Use 10wt% silver nitrate solution to impregnate an appropriate amount of zeolite molecular sieve. Simply immerse the zeolite molecular sieve completely in the silver nitrate solution for 3 hours to obtain Ag-zeolite molecular sieve modified material; dissolve 4.11gAgNO3 and 3.57g2-aminoterephthalic acid in 150ml of N,N-dimethylformamide; then add 50g of Ag-zeolite molecular sieve, shake and stir evenly, transfer the resulting mixture to a stainless steel autoclave, heat at 120℃ for 18h, cool the product after the reaction, centrifuge, collect the powder, and then immerse the powder in methanol solution for several times, and finally vacuum dry at 100℃ for 8h to obtain the final product, MOFs-loaded zeolite molecular sieve composite material. The final product is placed in a muffle furnace, calcined and activated at 200℃ for 8h under nitrogen as protective gas for testing.
[0038] Example 3
[0039] The preparation method of the MOFs-loaded zeolite molecular sieve composite material of this embodiment is as follows:
[0040] Use 15wt% silver nitrate solution to impregnate an appropriate amount of zeolite molecular sieve. Simply immerse the zeolite molecular sieve completely in the silver nitrate solution for 4 hours to obtain Ag-zeolite molecular sieve modified material; dissolve 2.19g AgNO3 and 1.93g 2-aminoterephthalic acid in 80ml N,N dimethylformamide; then add 20g of Ag-zeolite molecular sieve, shake and stir evenly, transfer the resulting mixture to a stainless steel autoclave, heat at 100℃ for 8h, cool the product after the reaction, centrifuge, collect the powder, and then immerse the powder in methanol solution for washing several times, and finally vacuum dry at 80℃ for 6h to obtain the final product, MOFs-loaded zeolite molecular sieve composite material. The final product is placed in a muffle furnace, calcined and activated at 160℃ for 4h under nitrogen as protective gas for testing.
[0041] Example 4
[0042] The preparation method of the MOFs-loaded zeolite molecular sieve composite material of this embodiment is as follows:
[0043] Use 20wt% silver nitrate solution to impregnate an appropriate amount of zeolite molecular sieve. Simply immerse the zeolite molecular sieve completely in the silver nitrate solution for 5 hours to obtain Ag-zeolite molecular sieve modified material; dissolve 5.1g AgNO3 and 3.99g 2-aminoterephthalic acid in 200ml N,N dimethylformamide; then add 50g of Ag-zeolite molecular sieve, shake and stir evenly, transfer the resulting mixture to a stainless steel autoclave, heat at 110℃ for 12h, cool the product after the reaction, centrifuge, collect the powder, and then immerse the powder in methanol solution for several times, and finally vacuum dry at 100℃ for 8h to obtain the final product, MOFs-loaded zeolite molecular sieve composite material. The final product is placed in a muffle furnace, calcined and activated at 200℃ for 8h under nitrogen as protective gas for testing.
[0044] The materials prepared in Examples 1-4 and Comparative Example 1 were used as test samples, and the materials were characterized using a BET specific surface area analyzer. The results are shown in Table 1.
[0045] Table 1
[0046] Sample <![CDATA[BET / (m 2 / g)]]> Example 1 1425 Example 2 1334 Example 3 1397 Example 4 1298 Comparative Example 1 1099
[0047] The data in Table 1 show that the MOFs-loaded zeolite molecular sieve composite material of the present invention has a large specific surface area, which is as high as 1298-1425 m 2 / g.
[0048] The materials prepared in Examples 1-4 and Comparative Example 1 were used as test samples to test their radon penetration ability. First, all test samples were placed in an oil bath at 130°C, N2 purged for 2 hours, and degassed and activated for 12 hours under vacuum conditions of 10Pa. Then, 1g of each activated sample was weighed in a vacuum glove box and loaded into the sample loading column respectively, and the radon concentration change of the circulation system was tested with a cycle of 10 minutes. After about 3 hours, on the premise of ensuring the stability of the instrument test, the material was connected to the drying column, and the dynamic adsorption data of the test material on radon was recorded.
[0049] Adsorption amount: Q = ∫∫(ct×F×t)dcdt / m (F is the gas flow rate controlled in the test procedure (mL / min); m is the mass of the adsorbed sample (g); t is the adsorption time (min); ct is the radon concentration measured at time t (Bq / m3); Q is the radon adsorption amount of the material calculated by the integrated concentration-time (Bq / g), which reflects the adsorption capacity of the material for radon gas).
[0050] Dynamic adsorption coefficient: kd = Q / c0 (kd is the dynamic adsorption coefficient (L / g), which normalizes the test influencing factors such as initial concentration, mass and gas flow, and reflects the material's adsorption capacity for radon gas).
[0051] Adsorption efficiency: η = (ct / c0) × 100% (η is the adsorption efficiency (%), which refers to the ratio of the radon concentration detected at the outlet when adsorbed to the lowest equilibrium point to the radon concentration detected at the outlet after final adsorption saturation. It can also be understood as the maximum depth that can remove radon gas under the same conditions. The larger the value, the stronger the material's adsorption capacity for radon. It is a parameter that reflects the material's ability to adsorb and bind radon).
[0052] Half penetration time: τ = kd × m / F (τ is the half penetration time (min), which refers to the time from the beginning of the airflow passing through the adsorption material to the penetration of 50% saturation point during the radon adsorption process of the material. It is also a parameter that reflects the material's ability to adsorb radon).
[0053] The results are shown in Table 2.
[0054] Table 2
[0055] Sample Dynamic adsorption coefficient / (L / g) Adsorption efficiency / % Half penetration time / min Example 1 10.17 93.5% 83 Example 2 8.22 89.9% 61 Example 2 9.14 87.3% 72 Example 4 8.55 81.4% 55 Comparative Example 1 5.97 50.6% 38
[0056] The data in Table 2 show that the absorption efficiency of the MOFs-loaded zeolite molecular sieve composite material for radon gas can reach 81.4-93.5%, and the adsorption efficiency is relatively high, reflecting its relatively high adsorption and binding capacity for radon gas. The semi-penetration time is 55-83 minutes, and the penetration time is relatively long, that is, the contact time between the zeolite molecular sieve composite material and radon gas is prolonged, which improves the adsorption effect to a certain extent, further reflecting its relatively high adsorption capacity for radon gas.
[0057] Example 5
[0058] The preparation method of the MOFs-loaded zeolite molecular sieve composite material of this embodiment is as follows:
[0059] Use 5wt% silver nitrate solution to impregnate an appropriate amount of zeolite molecular sieve. Simply immerse the zeolite molecular sieve completely in the silver nitrate solution for 4 hours to obtain Ag-zeolite modified material; dissolve 3.79g AgNO3 and 2.93g 2-aminoterephthalic acid in 50ml N,N dimethylformamide; then add 75g of Ag-zeolite molecular sieve, shake and stir evenly, transfer the resulting mixture to a stainless steel autoclave, heat at 130℃ for 24h, cool the product after the reaction, centrifuge, collect the powder, and then immerse the powder in methanol solution for several times, and finally vacuum dry at 120℃ for 10h to obtain the final product, MOFs-loaded zeolite molecular sieve composite material. The final product is placed in a muffle furnace, calcined and activated at 160℃ for 5h under nitrogen as protective gas for testing.
[0060] The present invention uses zeolite molecular sieve as a base material, in-situ grows material MOFs, and synergizes the pore size advantages of zeolite molecular sieve and MOFs to prepare a composite material that is beneficial to the radon adsorption effect; the present invention also loads silver ions on the zeolite molecular sieve in advance, so that the in-situ growth of Ag-MOF is more stable and uniform, and the final adsorption material significantly improves the adsorption capacity of radon, thereby broadening the application of the adsorption material in the field of radon adsorption.
[0061] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention. The techniques, shapes, and structural parts not described in detail in the present invention are all known technologies.
Claims
1. A zeolite molecular sieve composite material loaded with MOFs, characterized in that: The invention comprises the following raw materials: solid AgNO3, 2-aminoterephthalic acid, N,N-dimethylformamide, and Ag-zeolite molecular sieve, wherein the usage ratio of the solid AgNO3, 2-aminoterephthalic acid, N,N-dimethylformamide, and Ag-zeolite molecular sieve is (0.012-0.037) mol: (0.009-0.026) mol: (50-300) ml: (20-75) g; The preparation method of the MOFs-loaded zeolite molecular sieve composite material comprises the following steps: The zeolite molecular sieve is added into the silver nitrate solution and soaked for 3 to 5 hours, and filtered to obtain the Ag-zeolite molecular sieve; Solid AgNO3 and 2-aminoterephthalic acid were dissolved in N,N-dimethylformamide, and Ag-zeolite molecular sieve was added. The mixture was shaken and stirred evenly. The obtained mixture was transferred to a stainless steel high-pressure reactor and heated at 110-130°C for 12-24 hours. After the reaction, the product was cooled and centrifuged to collect the powder. The powder was then immersed in methanol solution for washing and vacuum dried at 80-120°C for 6-10 hours to obtain a zeolite molecular sieve composite material loaded with MOFs.
2. The MOFs-loaded zeolite molecular sieve composite material according to claim 1, characterized in that: The concentration of silver nitrate in the silver nitrate solution is 5-20 wt %.
3. The MOFs-loaded zeolite molecular sieve composite material according to claim 2, characterized in that: The preparation method further comprises placing the obtained MOFs-loaded zeolite molecular sieve composite material in a muffle furnace, using nitrogen as a protective gas, and calcining and activating at 160-200° C. for 4-8 hours.
4. Use of the MOFs-loaded zeolite molecular sieve composite material according to any one of claims 1 to 3 in radon gas adsorption materials.
Citation Information
Patent Citations
Framework material with Ag nanoparticle compound, preparation method and application
CN113385148A
Ag-loaded MOF composite material as well as preparation method and application thereof
CN117772121A